Differences in Indonesian Banking Financial Performance Before and After OJK Regulation Implementation Concerning Financial Technology - Anindya Anindya; Kartini Kartini (International Journal of Social Service and Research (IJSSR), 2023)
This study aims to analyse differences in banking financial performance in Indonesia before and after the issuance of OJK regulations on financial technology. This research is a quantitative study using a sample of 37 banking companies listed on the Indonesia Stock Exchange. The data used is secondary data obtained from annual reports for the period 2014-2017 before the issuance of OJK regulations and 2018-2021 after the issuance of OJK regulations. The analytical method used is the Wilcoxon Signed Rank Test on the variables ROA, ROE, BOPO, CAR and LDR. The results of this study indicate that the ROA, ROE, and CAR variables have a greater value after the regulation on financial technology, the BOPO variable has a smaller value after the regulation on financial technology and the LDR variable has a smaller value after the regulation on financial technology.